HUBUNGAN PENGETAHUAN DAN SIKAP KELUARGA TERHADAP PENCEGAHAN DYSPEPSIA DI DESA MATITI I KECAMATAN DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN TAHUN 2024 - Simamora, Rouli DF; Tambunan, Glorya; Br.Lumban Tobing, Tiara Pebrina; Banjarnahor, Jefri (Jurnal STIKes Kesehatan Baru, 2024)
Background: Dyspepsia is one of the factors that is a health problem in the community. This is a health problem that becomes an emergency unit channel on physical examination found a feeling of tenderness in the epigastric area leading to a diagnosis of gastritis. Purpose: The purpose of this study was to determine the Relationship between Knowledge and Community Attitudes Towards Dyspepsia Prevention. This type of research is quantitative research with an ascendental sampling design looking at the relationship between independent variables (knowledge, attitudes) with dependent variables (dyspepsia prevention) and then analyzing the data using a frequency distribution table, namely measurements at the same time to determine "The Relationship between Knowledge and Attitudes of the Community Aged 45-65 Years Towards Dyspepsia Prevention" which became respondents 42 people, 22 women and 20 men. Results: The results of this study indicate a relationship between Knowledge and Chi-Square with a confidence level of 90% (a = 0.10) and df = 2 obtained Square count (7.356) > Square Table (4.605), there is a relationship between knowledge and prevention of dyspepsia syndrome. By using the Square Test count (7.106) > Square Table (2.705), then Ha is accepted, Ho is rejected, meaning there is a relationship between attitude and Prevention of Dyspepsia Syndrome. It is expected that respondents will be more active in learning about the prevention of dyspepsia. It is expected that the local government and health workers will conduct socialization and promotion/counseling about the prevention of dyspepsia